Drgania Uderzeniowe Dwu Niezależnych Układów - Cempel, C. (Engineering Transactions, 1971)
In this work presented is the percussive vibration of two coupling systems by unilateral percussive forces. Using the method of Laplace transformation, the equation of movement is solved, proving that this system may be used as a percussive damper.Also determined are the areas of vibrations with impacts and optimal range of work for the system under consideration.